Adequacy level of energy and macronutrients for 3rd year students of the Food Technology Departement, Itera - Isnaini Rahmadi; Dea Tio Mareta; Dina Fithriyani (Journal of Science, Technology, and Visual Culture, 2021)
Macronutrients are composed of protein, fats, and carbohydrates. Current conditions indicate a malnutrition, which is undernourishment and overnourishment. This problem can also be experienced by college students. Student high activity and mobility are thought to affect the accomplishment of daily nutrition. Therefore, there was need to be measures of the quantity and type of nutrients consumed by the method of food recall. This method is used to determine the energy and macronutrient adequacy of students. This study aimed to obtain scientific data related to energy and macronutrients adequacy for students of Sumatra Institute of Technology (ITERA). The research subjects were 3rd year (age group 19-29 years) students of the Food Technology Departement, ITERA, which consisted of 22 students. In general, the average intake of energy and macronutrients of the subjects did not meet the nutrient adequacy level. Of the 22 research subjects, 15 of them experienced a severe energy deficit, 5 with moderate deficit nutritional, and 1 subject was in a mild deficit condition. The distribution of protein intake of research subjects also did not meet the nutrient adequacy level. Of the 22 research subjects, 6 of them experienced a severe deficit of protein, 1 subject had moderate protein nutritional status, and 4 subjects each had a mild deficit and excessive. The distribution of fat and carbohydrate research subjects has not met the nutrient adequacy level.